Evaluating the energy-water-food nexus in Qatar: Balancing crop imports and local production - Shannak, Sa’d; Jovanovic, Raka; Sanfilippo, Antonio; Namany, Sarah; Kafi, Abdellah; Al-Ansari, Tareq (Energy nexus, 2025)
•The relationship between crop imports and local production strongly impacts the energy water nexus and national food security strategies.•With three import partners, the optimal distributions are 40 %, 30 %, and 30 % when minimizing cost based on 2022 prices.•With more import partners, distribution becomes price-dependent, in- dicating a need for enhanced government coordination.•Optimizing both imports and local production can significantly reduce costs while enhancing food security.•Implementing the recommendations of Qatar National Food Security Strategy leads to cost reductions and a more balanced import strategy. Agriculture accounts for approximately 70 % of the global water demand and 30 % of the global energy demand. Finding an optimal balance in the provi- sion of food through imports or local production is therefore crucial in secur- ing energy and water sustainability. The literature on this subject has mostly focused on either local production or import strategies, and there is a need to integrate these elements into a unified framework. We address this need by developing a novel mathematical model that performs a nuanced analysis of self-sufficiency rates, price differentials, and import patterns through the integration of economic, environmental, and policy constraints. The ensu- ing analysis offers an evaluation of energy and water sustainability in the light of trade-offs between food imports vs. local production. Considering factors such as the energy required for water pumping in local crop produc- tion and the water footprint in the importing countries, the model elucidates the water and energy demands associated food imports and local production evaluating trade-offs between local production and imports. Results reveal that in scenarios with three import partners, the optimal distributions are consistently 40 %, 30 %, and 30 % when minimizing cost based on 2022 prices. However, with more import partners, distribution becomes price-dependent, indicating a need for enhanced government coordination and a more holistic approach to balancing local production and imports that accounts for energy and water resource constraints.